The self-medication behaviors of residents and the factors related to the consideration of drug efficacy and safety—A cross-sectional study in China - Ge, Pu; Zhang, Zi-Wei; Zhang, Jin-Zi; Lyu, Ke; Niu, Yu-Yao; Tong, Yu-Ting; Xiong, Ping; Ling, Rong; Li, Qi-Yu; Yu, Wen-Li; Min, He-Wei; Deng, Yu-Qian; et al. (Frontiers in Pharmacology, 2023)
Objectives: To make an investigation on the current status of Chinese residents’ self-medication behaviors and important considerations, and to explore the factors related to the considerations of drug efficacy and safety. Methods: Multi-stage sampling was used to conduct a cross-sectional investigation in China. The questionnaire that was used in the investigation included demographic sociological characteristics, health literacy scale-short form (HLS-SF), the 10-item Big Five Inventory (BFI-10), the EuroQol-5D visual analogue scale (EQ-5D VAS), self-medication status and important considerations when self-medicating. Descriptive statistics were performed, and the Chi-square test was used for univariate analysis. Log-binomial regression was used for multivariate analysis on whether residents regard drug efficacy or safety as an important consideration. Results: 9256 respondents were included in the data analysis. The self-medication rate of Chinese adults was as high as 99.1%. Paracetamol and other analgesics were the most common types of OTC medication that respondents purchased, followed by vitamins/minerals. Medical staff recommendations, drug safety and efficacy were the top three important considerations. The residents in the east, central and western regions who consider safety is 63.5%, 61.5% and 66.8% respectively. The proportion of curative effect was 60.2%, 55.7% and 61.4% respectively. Log-binomial regression showed that western respondents, retired people, those who mainly used ways including basic medical insurance for employees, commercial medical insurance, free medical treatment to cover their medical cost, respondents with high neuroticism, high health literacy were more likely to consider drug safety as an important factor (P<0.05). Eastern respondents, employed, main way of medical expenses borne was Out-of-pocket Payment, those with chronic disease were more likely to consider drug efficacy as an important factor (P<0.05). Female, respondents with high levels of agreeableness, conscientiousness, openness, and self-rated health status were more likely to regard both drug safety and efficacy as important considerations (P<0.05). Conclusion: Self-medication is practiced by most Chinese adults. Whether Chinese adults take drug efficacy or safety as an important consideration is related to their demographic and sociological characteristics, Big Five personality characteristics, health literacy and self-assessed health status. There is a need to strengthen the management of OTC drugs and public education about self-medication.